Sistem Pendukung Keputusan Pemilihan Supplier Bahan Baku Daging Menggunakan Metode Weighted Aggregated Sum Product Assesment (Waspas) (Studi Kasus : Kawasan Kuliner Sekar Mataram) - Agustin, Isnaini; Prasetyaningrum, Putri Taqwa (Jurnal Sains dan Teknologi (JSIT), 2022)
Individuals or businesses that supply or sell raw materials to other parties, whether individuals or businesses, so that they can be transformed into finished goods or services are referred to as suppliers. Suppliers must also make raw materials available to those who require them. Furthermore, the supplier must ensure that the raw materials are delivered to the buyer in good condition. The Sekar Mataram Culinary Area is located in Bantul City, Yogyakarta, specifically in Bangunjiwo Village. It is one of the business units owned by Village Owned Enterprises in Mbangun Kamulyan Bangunjiwo Village, which is growing and has received many offers from suppliers to supply raw meat materials to the Sekar Mataram Culinary Area. So far, the Sekar Mataram Culinary Area management has chosen raw meat suppliers through manual selection. Using the Weighted Aggregated Sum Product Assessment (WASPS) method, a Decision Support System will be built to determine the best raw material supplier and meet the restaurant's needs. This study requires criteria and alternatives to obtain a solution for making decisions on raw material supplier selection. This Decision Support System is web-based, making it more effective and efficient.